2015
DOI: 10.1080/10428232.2015.1017914
|View full text |Cite
|
Sign up to set email alerts
|

Social Workers and Social Justice During a Period of Intensive Neoliberalization: A Preliminary Investigation From the Republic of Ireland

Abstract: Despite the championing of social justice within the discourse of social work, some express concern that there has been a dilution in the profession's practical commitment to seeking a more just society. The article begins by defining social justice and then refers to a number of studies that have endeavored to identify whether or not social justice is being pursued by practitioners. It is argued that renewing efforts to achieve social justice is particularly relevant in times of intensive neoliberalization. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Studies show that social workers engaged with the poor face an emotional duality: compassion along with judgment, involvement along with avoidance, and solidarity along with rejection (Reingold & Liu, ). This duality may allude to the huge emotional struggle they face in order to reconcile the need to build empathetic, meaningful, and lasting working alliances with the families in the context of very constraining and oppressive institutional policies (Conneely & Garrett, ; Welbourne, ). In addition, research has also shown that social workers' emotions are influenced by the “theory of cultural poverty,” which emphasizes the intergenerational inheritance of pathological patterns, suggesting that acceptance of this theory affects their approach to and handling of families living in poverty (Castillo & Becerra, ) and increases the stigmatization and Othering of the families (McIntyre, Officer, & Robinson, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies show that social workers engaged with the poor face an emotional duality: compassion along with judgment, involvement along with avoidance, and solidarity along with rejection (Reingold & Liu, ). This duality may allude to the huge emotional struggle they face in order to reconcile the need to build empathetic, meaningful, and lasting working alliances with the families in the context of very constraining and oppressive institutional policies (Conneely & Garrett, ; Welbourne, ). In addition, research has also shown that social workers' emotions are influenced by the “theory of cultural poverty,” which emphasizes the intergenerational inheritance of pathological patterns, suggesting that acceptance of this theory affects their approach to and handling of families living in poverty (Castillo & Becerra, ) and increases the stigmatization and Othering of the families (McIntyre, Officer, & Robinson, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently there has been a renewed call to connect and integrate social work and politics. In a series of publications, scholars have claimed that in the current neoliberal political-economic and ideological context social workers have abandoned their involvement in influencing societal macro-level changes and have undergone a process of de-politicization (Conneely and Garrett, 2015; Featherstone et al, 2012; Nadan et al, 2015; O’Brien, 2011; Reisch and Jani, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…I argue that the social justice value base aspiration of the social work profession can contribute to struggles for social justice that challenge the neoliberal socio-economic context. This necessitates that the social work profession goes beyond the rhetorical affirmation of its value base and acknowledges the difficulties of attaining social justice (Conneely and Garrett, 2015). Also, at the same time, the social work profession should recognise the 26 possibilities of human agency to overcome those difficulties.…”
mentioning
confidence: 99%